Age relationship with incidence of proximal femur fracture at PKU Muhammadiyah Yogyakarta Hospital in 2022 - Arrozhi Muhammad Yusuf; Hikmawan Taufiek; Sambada Benni; Silvia Ipho; Latif Anwarudin; Wijaya Adi Indra; Kadarmo Dhiwangkoro Aji (BIO Web of Conferences)
Femoral fracture is a condition where there is a disturbance in the discontinuity of the femur bone which can be caused by accidents, degenerative and pathological processes. Based on Riskesdas data (2018), femoral fractures have the highest prevalence in cases of lower extremity fractures. Of the 92.976 cases that occurred, as many as 19.754 people suffered femoral fractures. With age, the risk of femoral fracture will increase, especially in the incidence of proximal femoral fractures. This study used an analytical descriptive method with a cross-sectional research design and a retrospective study. The subjects in the study were taken by total sampling method with a minimum number of 101 samples in the medical record. The analysis used in this study was univariate analysis with tabulation presentation (table) and bivariate analysis using a chi-square test. The results showed that the incidence of proximal femur fractures occurred most often in the age group over 40 years, which was 87 subjects (73,7%). There is a significant relationship between age and sex with the incidence of proximal femoral fracture at PKU Muhammadiyah Hospital Yogyakarta.